HUBUNGAN ANTARA PERBAIKAN GRADASI PASIR LOKAL DENGAN KUAT TEKAN DAN BIAYA BETON DI KEPULAUAN KARIMUN JAWA - Endroyo, Bambang (MEDIA KOMUNIKASI TEKNIK SIPIL, 2003)
Nowdays, civil work needs concrete in larger quantities, because it has several benefit characters. Karimunjawa Islands which is located on Java Sea, 90 kilometers North of Jepara and which has been becoming a developing tourism site, needs concrete building for infrastructure. Karimunjawa sand is not eligible for building structure, so a qualified guarantied concrete is very expensive because must use Java sand which must be brought up by ship. It is necessary to use some local material in large quantities for getting an economic concrete price. This research attempts to substitute Muntilan sand by gradual increasing in composition to get a qualified –economic concrete, and will find its relation to the cost. The substitution values starts from 0% to 100%. The mix-composition is 1:1.5:2.5, wcf 0.5, cement from Gresik company, and coarse aggregate from Karimunjawa (local) and from Jepara. Water from Karimunjawa. The price of material and labour wage are prevailed when research is being done. The result are: there is a relation between improvement of sand gradation with both of quality and cost of concrete. The larger the composition of substitution, the higher quality and the more expensive its cost becames. In the quality from fc’ 8.4 MPa tp 14.1 MPa, concrete using local crushed stone was 8.43% cheaper than concrete using Jepara crushed stone.